Changes in soil susceptibility to erosion under tillage and soil fertility management practices - Mesele, S.A. (Maximum Academic Press, 2024)
The degree to which soil is susceptible to erosion is measured as soil erodibility which can be influenced by different land management options. This study evaluated the dynamics of soil erodibility to tillage and soil amendments in a maize field under five consecutive cropping cycles. Tillage treatments were no-till, minimum, conventional, and grassland fallow (control). The soil amendment treatments used were no amendment (control), NPK, poultry manure (PM), and ½ NPK+ ½ PM and these treatments were applied to all the tillage treatments including no-till. The study showed that tillage and soil amendment interactions had significant effects on soil erodibility (p< 0.05). The mean erodibility values ranged from 13× 10− 3 to 24× 10− 3 Mg· h· MJ− 1· mm− 1 in the following order: control< conventional tillage< minimum tillage< no-till. For the soil amendments, erodibility varied from NPK> poultry manure= ½ NPK+ ½ PM> control (undisturbed grassland). Regardless of the type of soil amendment, the soil erodibility under conventional tillage was significantly lower than that under no-till and minimum tillage systems. The relationship between erodibility and easily measured soil parameters, such as% sand greater than 100 µm,% silt plus very fine sand, clay, and saturated hydraulic conductivity, were significant at p< 0.05. The higher contribution (86%) of sand and silt to the variation in erodibility indicates that any other indices of erodibility based on particle size distribution, apart from the nomograph, could satisfactorily predict erodibility values.